2006
DOI: 10.1111/j.1600-051x.2006.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a chlorhexidine dentifrice in orthodontic patients: a randomized‐controlled trial

Abstract: This blind and randomized-controlled trial analysed chlorhexidine dentifrices in relation to dental plaque, gingivitis, bleeding, calculus and enamel extrinsic staining development. Volunteers in fixed orthodontic therapy used the following dentifrices: 1100 ppmF, NaF (group A, n=27); experimental, 1100 ppmF, NaF and chlorhexidine 0.95% (group B, n=28); and experimental, chlorhexidine 0.95% (group C, n=28). At baseline, after 6, 12 and 24 weeks, clinical examinations were carried out. The gingivitis, bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 30 publications
4
33
0
11
Order By: Relevance
“…After 60 days, the clinical improvements observed in both groups were more compatible with studies that investigated the effect of a daily toothbrushing with a triclosan dentifrice [23,28,29] than studies with CHX [30][31][32]. In this study, the incorporation of 0.05% chlorhexidine in a dentifrice containing 0.3% triclosan (CHX/triclosan group) did not offer further benefits to gingival inflammation and plaque control in comparison with a dentifrice containing 0.3% triclosan (Triclosan group).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…After 60 days, the clinical improvements observed in both groups were more compatible with studies that investigated the effect of a daily toothbrushing with a triclosan dentifrice [23,28,29] than studies with CHX [30][31][32]. In this study, the incorporation of 0.05% chlorhexidine in a dentifrice containing 0.3% triclosan (CHX/triclosan group) did not offer further benefits to gingival inflammation and plaque control in comparison with a dentifrice containing 0.3% triclosan (Triclosan group).…”
Section: Discussionsupporting
confidence: 80%
“…Its dental plaque inhibition properties were first investigated by Schroeder [8], and it was confirmed as later by as an effective agent in preventing gingival inflammation and reduction of plaque by Löe and Schiott [9]. Since then, it has played a central role in research, being used in many vehicles such as gels, varnishes, chips, chewing gums, dentifrices and mouthwashes [10][11][12]. In dental practice, mouthwash is the most used form, though clinical studies has shown that CHX in dentifrices can also offer further benefits to oral health with less tooth discoloration [13].…”
mentioning
confidence: 99%
“…Las presentaciones son diversas y contemplan opciones tales como enjuagues bucales, geles o dentífricos, cuyo efecto depende en mayor medida de la cooperación del paciente. 32,33 Adicionalmente, de acuerdo con algunos reportes en la literatura, medidas adicionales como el uso de cepillos eléctricos con acción rotatoria en pacientes con tratamiento de ortodoncia remueven más placa y reducen la gingivitis más efectivamente que el cepillado manual. 34,35 Es necesario desarrollar programas preventivos que refuercen la calidad de los tratamientos y disminuyan los costos tanto biológicos como econó-micos para el paciente y puedan cumplir con los objetivos estéticos que cada vez son más frecuentemente buscados por los pacientes.…”
Section: Discussionunclassified
“…Remodeling of the bone is interrupted by inflammation (Cernochova et al, 2007). By Olympio et al (2006), the use of dentifrices containing chlorhexidine seems to be effective for the treatment of periodontitis in orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%